Percutaneous Coronary Intervention vs. Coronary Artery Bypass Grafting for Treating In-Stent Restenosis in Unprotected-Left Main: LM-DRAGON-Registry - Wańha, Wojciech; Bil, Jacek; Kołodziejczak, Michalina; Kowalówka, Adam; Kowalewski, Mariusz; Hudziak, Damian; Gocoł, Radosław; Januszek, Rafał; Figatowski, Tomasz; Milewski, Marek; Tomasiewicz, Brunon; Kübler, Piotr; et al. (Frontiers in Cardiovascular Medicine, 2022)
BACKGROUND: Data regarding management of patients with unprotected left main coronary artery in-stent restenosis (LM-ISR) are scarce. OBJECTIVES: This study investigated the safety and effectiveness of percutaneous coronary intervention (PCI) versus coronary artery bypass grafting (CABG) for the treatment of unprotected LM-ISR. METHODS: Consecutive patients who underwent PCI or CABG for unprotected LM-ISR were enrolled. The primary endpoint was a composite of major adverse cardiac and cerebrovascular events (MACCE), defined as cardiac death, myocardial infarction (MI), target vessel revascularization (TVR), and stroke. RESULTS: A total of 305 patients were enrolled, of which 203(66.6%) underwent PCI and 102(33.4%) underwent CABG. At 30-day follow-up a lower risk of cardiac death was observed in the PCI group, compared with the CABG-treated group (2.1% versus 7.1%,HR 3.48, 95%CI 1.01-11.8,p=0.04). At a median of 3.5 years (interquartile range (IQR) 1.3–5.5) follow-up, MACCE occurred in 27.7% versus 30.6% (HR 0.86, 95%CI 0.54-1.36,p=0.53) in PCI- and CABG-treated patients, respectively. There were no significant differences between PCI and CABG in cardiac death (9.9% versus 19.4%; HR 1.65, 95%CI 0.87-3.15,p=0.12), MI (7.9% versus 5.1%, HR 0.44, 95%CI 0.15-1.27,p=0.13), or stroke (2.1% versus 4.1%, HR 1.78, 95%CI 0.44-7.16,p=0.41). TVR was more frequently needed in the PCI group (15.2% versus 6.1%, HR 0.35, 95%CI 0.14-0.85,p=0.02). CONCLUSIONS: This analysis of LM-ISR patients revealed a lower incidence of cardiac death in PCI compared with CABG in short-term follow-up. During the long-term follow-up, no differences in MACCE were observed, but patients treated with CABG less often required TVR.